Mathematical Model and Numerical Simulation of Coalbed Methane Migration Considering the Adsorption Expansion Effect. (30th April 2022) - Xie, Jianlin; Yang, Shaoqiang; Li, Pengwei
Abstract : The influence of gas adsorption and desorption on the volumetric strain of coal was measured by a self-designed, fluid–solid coupling triaxial coal adsorption deformation experimental system. The experimental results show that coal deformation has a threshold value with an increase in gas content. Before the gas content reaches the threshold value, coal deformation is not obvious. When the gas content reaches the threshold value, the deformation will increase sharply. At the same time, coal volume strain changes with coal gas content in accordance with exponential law ε  =  ε 0(e ϒc -1). Based on the experimental results, considering the coupling effects of heat transfer, water seepage, coal and rock mass deformation, and coalbed methane desorption and seepage, a mathematical model of heat transfer–deformation–seepage coupling coalbed methane migration was established, and a numerical simulation study was carried out on the heat injection-enhanced coalbed methane mining project. The results show that (1) With continuous heat injection, the gas in the coal seam is rapidly desorbed, and the adsorbed gas content forms an elliptical funnel that extends from the extraction hole to the deep part of the coal body and takes the fracturing crack as the center to the upper and lower boundaries of the coal seam. At day 30, the adsorbed gas content in the whole drainage area has decreased to 0.1 m 3 / t within 2m from the fracture zone. (2) On the basis of considering the gas adsorption expansion effect, the strain of the coal body decreases from roof to floor. With the increase in the heat injection time, the strain value will also increase, and the strain increase will decrease. When the heat injection is 30 days, the maximum strain at the roof is 0.015. The research results have important guiding significance for predicting coal rock deformation and determining gas extraction efficiency in the process of heat injection-enhanced coalbed methane extraction.